A study on financial performance of Shell Refining Company (Federation of Malaya) / Siti Nurulsyuhada Rosnan - Rosnan, Siti Nurulsyuhada (2012)
The focus of this study is to investigate on the financial performance Shell Refining Malaysia Berhad. The researcher focuses on the financial analysis tools in analyzing the company’s performance. There are five analysis tools which is comparative financial statement analysis, common size financial statement analysis, ratio analysis,. The researcher focus only on the three analysis tools mentioned above. This study will focus on the financial analysis of the company for the past five year’s period range from 2006 to 2010.The company’s annual report is examine for the reporting of valuating financial ratios. The objective of this study is to provide relevant information about the financial position, performance and changes in financial position of the organization besides enhance the companies’ profitability. This study will use the secondary data which is the company’s annual report of Shell Refining (Federation of Malaya) Malaysia Berhad.